2016
DOI: 10.1111/pace.12955
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Use of the Subcutaneous Implantable Cardioverter Defibrillator and a Permanent Pacemaker

Abstract: In unique situations, combined use of the S-ICD and a permanent pacemaker may be preferable to alternative options. In our experience, this approach was successful in varying conditions including complex congenital heart disease, recurrent device infection, and limited vascular access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…In over 83% of cases they were associated with the limitations of S-ICD systems, such as the need for pacing, CRT, and the possibility to deliver ATP. At present, S-ICD is not conventionally an option for patients who require permanent pacing; nonetheless, when combined with a transvenous pacemaker, such a combination is feasible [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In over 83% of cases they were associated with the limitations of S-ICD systems, such as the need for pacing, CRT, and the possibility to deliver ATP. At present, S-ICD is not conventionally an option for patients who require permanent pacing; nonetheless, when combined with a transvenous pacemaker, such a combination is feasible [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…8 More recently, Huang et al identified 4 S-ICD patients with a coexisting transvenous pacemaker who did not experience any trouble during follow-up. 9 Other sporadic problem-free cases have been reported by Porterfield et al and Steinberg et al 10,11 This very initial experience provides some evidence that a transvenous pacemaker/CRT device can be used safely with an S-ICD. In order to minimize risks of crosstalk between the implanted devices, however, some steps are recommended.…”
mentioning
confidence: 71%
“…More recently, Huang et al . identified 4 S‐ICD patients with a coexisting transvenous pacemaker who did not experience any trouble during follow‐up . Other sporadic problem‐free cases have been reported by Porterfield et al .…”
Section: Editorial Commentmentioning
confidence: 84%
“…It has been reported that venous occlusion is observed in 26-33% of patients with previous transvenous leads of ICDs or pacemakers. [1][2][3] Prior to our study, there have been some reports of patients with previous transvenous or epicardial pacemakers in whom S-ICD was newly implanted and used together, [7][8][9][10][11][12][13][14] but the clinical experience is still limited. The pooled cohort of the 2 largest S-ICD trials, the Food and Drug Administration-mandated U.S. Investigational Device Exemption (IDE) Registry and the Evaluation oF FactORs ImpacTing CLinical Outcome and Cost EffectiveneSS of the S-ICD (EFFORTLESS S-ICD) registry, excluded patients with unipolar pacemakers or implanted devices that revert to unipolar pacing and included only 19 individuals who had a bipolar pacemaker prior to S-ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…6) One disadvantage, though, is that S-ICDs cannot provide pacing therapy lacking transvenous leads. There have been several case reports of patients with previous transvenous or epicardial pacemakers, in whom S-ICD was newly implanted and used together, [7][8][9][10][11][12][13] as well as of prior cardiac resynchronization therapy (CRT) with an S-ICD. 7,14) In clinical settings, the number of such patients whose venous access cannot be secured, resulting in no choice other than the concomitant use of pacemakers and S-ICDs, might in-crease in the future.…”
mentioning
confidence: 99%